Legal Protection of Persons with Hearing Disabilities Associated with the Obligation to Read Deeds (Verlijden) For Notaries in Making Notarial Deeds - Rahmatulloh, Rahmatulloh; Herlindah, Herlindah; Jauharoh, Arini (International Journal of Business, Law, and Education, 2024)
The Security Office Act (UUJN) contains legal provisions regarding the authenticity of recorded documents that are read but not heard by persons with disabilities; especially Article 16, Section 1, paragraph m of Law No. 16. Law No. 2 of 2014 on the Notary Public (UUJN) Regulation. The research questions of this study are: (1) How are certified texts read but not heard by deaf people; In this study, research methods based on law and theory are used. The data collection process was carried out through literature research. The results of the research show that: (1) Reading the work by the author with the help of a translator is valid if the actual production still complies with the regulations determined by the notary law. (2) The notary must be legal and impromptu, must include information on the official translation promise that the notary knows how to translate, and the face document at the end of the residence document. Making the work done by the notary on behalf of the hearing impaired people realistic, thus obtaining the legal rights of the hearing impaired as a service to the users and binding the legal goods on both parties, especially third parties.